Avaliação da capacidade imunomodulatória de isolados de Lactobacillus bovinos (L38 E L36) em modelo experimental murino desafiado por Salmonella enterica subsp. enterica sorovar Typhimurium - Raphael Steinberg da Silva (2012)
Developed countries have imposed severe restrictions on the use of antibiotics as growth promoters in cattle. In this scenario, probiotics stand out as potential substitutes for these traditional growth promoters. Probiotics are "live microorganisms which when administered in adequate amounts, confer health benefits to the host." Their mechanisms of action are: direct antagonism against pathogens, increased efficiency of intestinal barrier and immunomodulation. In addition, probiotcis have important protective effects against various diseases, such as salmonellosis which represents a major cause of economic losses in livestock production. There are several bacterial genera with probiotic effect, especially Lactobacillus. As most of theprobiotic preparations for animal nutrition uses human probiotic strains there are few knowlegment of the effect of potentially probiotic bacteria of bovine origin on the host health. Therefore, the objective of this study was to evaluate the ability of colonization and immunomodulatory effect of isolates L36 (L. acidophilus) and L38 (L. salivarius), obtained from feces of calves. To evaluate the ability of colonization and immunomodulatory effect, gnotobiotic mice were obtained by monoassociation of isolates L36 and L38 in germ-free animals and accompanied population levels in the faeces over ten days. The protective imunomodulatorory effect of the isolates were evaluated in conventional animals treated with L36 and L38 and challenged with Salmonella enterica subsp. enterica serovar Typhimurium. It was evaluated general health parameters (weight variation, hepatic and spleenic indexis), production of IgA in the intestinal mucosa, histological aspect of bowel and liver and cytokine profile (IL5, IL6, IL10, IL -12-p40, IL17a, Ifng, Tgfb1 and Tnfa) along the intestine portions by RT-qPCR. The isolates L36 and L38 were able to colonize the intestinal mucosa of germ-free animals, presented high population levels in feces (8.87 ± 0.38 log CFU / g of feces for L38 and 8.39 ± 0.83 log CFU / g of feces for L36). Furthermore, in gnotobiotic animals, L36 appears to stimulate a cellular response in the intestinal mucosa, type TH17, it leads to significant increases (p <0.05) of expression levels of IL6, IL17a, Tgfb1 and Tnfa. However, L38 produced a cytokine profile (increased IL5,IL10, IL12b, IL17a, Ifng and Tgfb1) in the intestine indicative of a balance between TH and Treg type responses. The isolates L36 and L38 showed up safe due to the absence of parameters that are indicative of local or systemic infection. Both isolates were unable to stimulate the production of IgA in the mucosa, both in gnotobiotic and conventional animals but they decreased IgA production in Salmonella-challenged animals. There was no protection afforded by isolates against Salmonella infection. However, in Salmonella-challenged animals, L38 led to high production of IL10 along all the intestine. Therefore, L36 and L38 showed up safe and produce different immunomodulatory profiles in the mucosal.